Design of the wastewater treatment system of an office building - Rizky Raissha; Mas Agus Mardyanto (Sustinere: Journal of Environment and Sustainability, 2017)
The MIPA Tower office building, an eleven-storey building, which is located in the area of Institut Teknologi Sepuluh Nopember Surabaya, is under construction. The building will be utilized for offices, classrooms, and laboratories. In the operation of the building, domestic and laboratory wastewater will be produced. This wastewater contains compounds that can pollute the environment. A design of domestic and laboratory wastewater treatment system is conducted. The system comprises of a neutralization tank, a grease trap, an equalization tank, an anaerobic filter, and an activated carbon and silica sand filter. The steps of the design are (i) collecting primary data and secondary data, (ii) calculating the engineering design, (iii) drawing the Detailed Engineering Design (DED), and (iv) calculating the bill of quantity and budget. The conclusion of this design is that the treatment plant will treat a mixture of domestic and laboratory wastewater. The dimension of each unit is as follows: (i) the neutralization tank (Ã˜ = 0.65 m, H = 0.43 m), (ii) the grease trap (4 m x 2 m x 1 m), (iii) the equalization tank (10.5 m x 5.5 m x 2.5 m), (iv) the septic tank (4.5 m x 4 m x 2.5 m), (v) the six-compartment anaerobic filter (2.25 m x 4 m x 2.5 m), and (vi) the filter with activated carbon (H = 50 cm), silica sand (H = 150 cm), and gravel (H = 10 cm), with the diameter of the tank is 1.5 m.